Effect Of Foreign Direct Investment (FDI) On Manufacturing Output In Nigeria (1981 – 2016). - Idoko, Cletus Usman; Taiga, Usio Uchechi (Advances in Social Sciences Research Journal, 2018)
This study examined the effect of Foreign Direct Investment (FDI) on manufacturing sector output growth in Nigeria for the period of 1981 to 2015. The research was guided by two research questions and objectives. The Vector Auto Regression (VAR) technique and Johansen Co-integration test were employed for testing the hypotheses of the study. The VAR analysis empirical results from the impulse response function and variance decomposition test shows that FDI had a positive but minimal effect on the manufacturing sector output in Nigeria. The Co-integration test results show that there exist a long-run relationship between FDI and the manufacturing sector output growth in Nigeria. To improve on the gains of FDI on the manufacturing sector, the study recommends that government should carryout infrastructural development, like power supply to improve the absorptive capacity of manufacturing firms.Also there should be a clear guideline in government policy regarding priority sectors such as the manufacturing sector where foreign investments should be directed in the country.It was also recommended that effort should be made to increase productivity in the manufacturing sector by upgrading its technologies; and on the issue of corruption and diversion of funds, among others were proffered.